Effectiveness of physical therapy in axillary web syndrome after breast cancer: a systematic review and meta-analysis. - González Rubino, Jesús Baltasar; Viñolo-Gil, Maria Jesús; Martín-Valero, Rocío (Springer Nature, 2023)
The axillary web syndrome (AWS) is a surgical breast cancer sequel that limits the functionality of the patient and delays the protocol times of application of cancer treatments. This implies a long period of discomfort and limitations for the user. Objective To investigate the different physiotherapy treatments for the AWS and how effective they are. Methods A systematic review based on PRISMA protocol and registered in PROSPERO(CRD42021281354)was conducted. The research was performed using PubMed, Scopus, CINAHL, PEDro, and Web of Science databases during January 2022 and March 2022. All randomized controlled trials and controlled clinical trials were included in this review. Results A total of 188 articles were identified, with 9 studies selected for the systematic review. These studies basically propose treatments based on exercises and stretching, manual therapy, and the combination of manual therapy and exercises. Conclusions Exercise and stretching are the most effective therapies within the field of physiotherapy for the rehabilitation of axillary web syndrome. They restore range of motion faster, reduce pain, improve quality of life, and reduce disabilities. Manual therapy, scar massage, and myofascial release could help improve outcomes but with worse results. The meta-analysis conclusion is that pain is the only outcome with a significant reduction after the application of physiotherapy treatments − 0.82 [− 1.67; 0.03]. This conclusion is drawn from the only three studies with small sample sizes.
Keywords: Mamas - Cáncer - Ejercicios terapéuticos; Breast neoplasms; Lymphatic system; Range of motion; Functional status; Axillary web syndrome; Axillary lymphadenectomy